Visualizing empire : Africa, Europe, and the politics of representation - Peabody, Rebecca; Peabody, Rebecca; Nelson, Steven; Nelson, Steven; Thomas, Dominic Richard David; Thomas, Dominic Richard David (Issues & debates / Getty Research Institute, 2021)
French Colonial Collections at the Getty Research Institute / Frances Terpak -- The History and Future of ACHAC / Pascal Blanchard and Dominic Thomas -- Decolonizing the ACHAC Collection / Patricia Morton -- Fragments of Empire : Ephemera, Representation, and the Dynamics of Colonial Memory / Charles Forsdick -- Intersecting Legacies of bandes dessinées and Belgian Colonial Instruction : Les aventures de Mbumbulu in Nos images (1948-55) / Peter J. Bloom -- French Colonialism : The Rules of the Game / Dominic Thomas -- The Myth of the Sahara / Michelle H. Craig -- Representations of the tirailleurs sénégalais and World War I / David Murphy -- On Posters and Postures : Colonial Enlistment Posters and the Nationalist Imagination in France / Lauren Taylor -- La France et ses colonies : Mapping, Representing, and Visualizing Empire / Steven Nelson.